2019
DOI: 10.3390/jcm8111948
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Excretion of N1-Methylnicotinamide, as a Biomarker of Niacin Status, and Mortality in Renal Transplant Recipients

Abstract: Renal transplant recipients (RTR) commonly suffer from vitamin B6 deficiency and its functional consequences add to an association with poor long-term outcome. It is unknown whether niacin status is affected in RTR and, if so, whether this affects clinical outcomes, as vitamin B6 is a cofactor in nicotinamide biosynthesis. We compared 24-h urinary excretion of N1-methylnicotinamide (N1-MN) as a biomarker of niacin status in RTR with that in healthy controls, in relation to dietary intake of tryptophan and niac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…The WHO and the EFSA recommend the 24-h urinary excretion of N 1 -MN for laboratory assessment of niacin nutritional status accordingly [3,4]. In a previous study, we found that N 1 -MN excretion is clearly reduced in RTR compared to healthy kidney donors [12]. The fact that this is paralleled by a significant elevation of 2Py excretion in the present study, raises speculation that enhanced enzymatic conversion of N 1 -MN to 2Py by AOX1 may be present in RTR.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…The WHO and the EFSA recommend the 24-h urinary excretion of N 1 -MN for laboratory assessment of niacin nutritional status accordingly [3,4]. In a previous study, we found that N 1 -MN excretion is clearly reduced in RTR compared to healthy kidney donors [12]. The fact that this is paralleled by a significant elevation of 2Py excretion in the present study, raises speculation that enhanced enzymatic conversion of N 1 -MN to 2Py by AOX1 may be present in RTR.…”
Section: Discussionmentioning
confidence: 85%
“…Baseline characteristics of RTR and the total cohort of kidney donors were compared by means of t, Mann-Whitney, and Chi-Square tests, of which age, sex, body surface area, N 1 -MN excretion and eGFR have been reported previously [12]. Crude associations of 2Py and N 1 -MN excretion with intake of niacin equivalents were investigated with linear regression analyses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations